Optimalisasi Penerapan Standard Operating Procedure (SOP) dalam Meningkatkan Pelayanan Front Office Department di Four Star By Trans Hotel, Renon, Bali - Ni Luh Putu Sri Antari; Trianasari Trianasari; Luh Putu Triyanti Ariestiana Dewi (Dharma Ekonomi, 2025)
This study was conducted at Four Star by Trans Hotel, Renon, Bali which discussed the Optimization of the implementation of standard operating procedures (SOP) in improving front office department services. The purpose of this study was to determine the implementation of Front Office SOPs at Four Star by Trans Hotel and how SOPs can improve service quality. Researchers used primary and secondary data to support this study. Data collection techniques used were observation, interviews and document studies. The method used was a qualitative descriptive method. The results of the study showed that the front office (bellboy, reservation, telephone operator, receptionist) had implemented existing SOPs and had provided the best service to guests, but not optimally, due to several reasons, one of which was the lack of front office staff. The dimensions used as a reference to measure how SOPs are implemented by the front office include reliability, responsiveness, certainty or guarantee, empathy, tangibles.